KAJIAN KARAKTER MORFOLOGI MIKROSPORA TEMBAKAU VIRGINIA YANG MENGALAMI CEKAMAN PELAPARAN DAN SUHU TINGGI SECARA IN VITRO - Wahidah, Baiq Farhatul (Teknosains: Media Informasi Sains dan Teknologi, 2014)
The effect of treatment combination by heat shock (34oC) and starvation medium on embryogenesis induction in microspore culture of selected genotype of Nicotiana tabacum L.cv. Virginia was examined. The microspores which were isolated aseptically by maceration and centrifugation, were cultured on starvation medium (B medium) without sugar and nitrogen during 6 days at 34oC. The culture contained relatively homogeneous population of developed stage microspore (late uninucleate stage). The viability and development of microspore was obsevered. DAPI (4,6-diamidino-2-phenylindole) was used to stain the nucleus. Stained microspores were examined under a fluorescence microscope. The result showed that during stress treatment by starvation and heat shock (34oC) the structure of microspore change into 3 types of embryogenic microspore. Type 1 was identical to the late uninucleate microspore stage; in type 2 the vacuole of microspore was fragmented and peripheral cytoplamic pocket contain the nucleus; and type 3 the nucleus was positioned in cytoplamic pocket in the centre of the microspore.